Assessing the impact of topography and land cover data resolutions on two-dimensional HEC-RAS hydrodynamic model simulations for urban flood hazard analysis - Yalcin, Emrah (Natural hazards (Dordrecht), 2020)
This study assesses the effects of topography and land cover data resolutions on the estimates of flood extent, inundation depths, flow velocities, and arrival times of a two-dimensional (2D) hydrodynamic HEC-RAS model under differently sized mesh structures, with the example of the urban floodplain of Kilicozu Creek (Kirsehir, Turkey). To analyse these effects under a wide range of data conditions, seven different resolution digital surface models (DSMs) (from 0.0432 to 10 m/pixel) and Manning’s roughness layers (MRLs) (from 2 to 25 m/pixel) are produced for the subject floodplain by processing the high-quality DSM and orthophoto of the Kirsehir city centre. Additionally, seven different computational point spacings (CPSs) (from 2 m × 2 m to 25 m × 25 m) are tested to evaluate changes in the model outputs depending on the dimensions of mesh grids. Simulations are carried out for 19 different DSM, MRL, and CPS configurations under the 500-year flood scenario. The simulation performed for the most detailed model configuration is utilised as the base model simulation to compare the performances of other simulations. The model simulation configurated with the 2 m cell size DSM, 10 m cell size MRL, and 10 m × 10 m CPS shows comparable performance to the base model simulation with a small loss in the accuracy of the estimates, indicating that very-fine-resolution (less than 2 m) topography and high-resolution (less than 10 m) land cover data may not be indispensable to produce reliable simulations with 2D urban flood modelling using HEC-RAS software.